2011
DOI: 10.1089/gtmb.2010.0222
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Polymorphisms on Chromosome 9p21 and Age of Onset of Coronary Heart Disease in Black and White Women

Abstract: Aim: Genome-wide association studies have identified variants on chromosome 9p21 that are associated with coronary heart disease (CHD). The relationship between these variants and the age of onset of CHD is less clear. The aim of this study was to examine the allelic frequencies and haplotype structure of eight single-nucleotide polymorphisms (SNPs) on chromosome 9p21 in ethnically diverse women. We also explored the relationship between 9p21 SNPs and the age of CHD onset. Results: There was considerable inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Relationships between bone disease and arterial calcification are well established, numerous studies report inverse relationships between bone mineral density (BMD) and atherosclerosis in EAs and AAs 4446 . The 9p21 region was previously associated with coronary artery disease susceptibility in predominantly European-derived populations 36, 47, 48 . AAs with excess European ancestry in this region had higher prevalence and/or higher levels of CAC.…”
Section: Discussionmentioning
confidence: 93%
“…Relationships between bone disease and arterial calcification are well established, numerous studies report inverse relationships between bone mineral density (BMD) and atherosclerosis in EAs and AAs 4446 . The 9p21 region was previously associated with coronary artery disease susceptibility in predominantly European-derived populations 36, 47, 48 . AAs with excess European ancestry in this region had higher prevalence and/or higher levels of CAC.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies showed a strong linkage disequilibrium (LD) between the two SNPS, rs10757278 and rs2383206 ( 26 , 34 ). Doria et al ( 26 ) showed that the G allele of rs2383206 was associated with CAD regardless of the rs10757278 allele that was present on the same haplotype, whereas the A allele of rs10757278 was protective only when it occurred together with the protective allele of rs2383206.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the two SNPs rs10757278 and rs2383206 on the susceptibility locus 9p21 with CAD in multiple cohorts of European descent was demonstrated by Shen et al ( 35 ). Beckie et al ( 34 ) examined the allelic frequencies and haplotype structure of genetic variants on chromosome 9p21 in a cohort of black and white women with CHD and examined the relationship of these genetic variants with the age of onset of CHD. Few blacks as a different from whites, had the risk genotype for rs10757278 SNP, and only 12.5% of blacks had the risk genotype (GG) for rs2383206 compared with 35.2% of whites ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This SNP was significantly associated with the risk of CHD in a Northern Indian population [23] and in African American women [24]. Genetic variation and differences in life styles among populations probably explain the population disparities in the association of this SNP and susceptibility to CHD.…”
Section: Discussionmentioning
confidence: 99%